Dermoscopic Features of Alopecia Patient - Paramita, Kartika; Listiawan, M. Yulianto; Rahmadewi, Rahmadewi (Faculty Of Medicine Airlangga University, 2015)
Backgroud: Alopecia is hair loss of the scalp that occurs in mostly men and about 30% of women during their lifetime. Prevalence of alopecia is increased along with age in both men and women. Using of dermoscope can help the diagnostic accuracy and avoid scalp biopsy for diagnosis. Purpose: Identifying dermoscope examination results and determine the pathophysiology of dermoscope features. Methods: Cross sectional and descriptiove observational study to all of alopecia patients who fulfilled the inclusion criteria at outpatient clinic Dr. Soetomo General Hospital Surabaya in December 2014 through February 2015 performed dermoscope examination Result: There were 20 patients who fulfilled the inclusion criteria, consisted of 3 patients with androgenetic alopecia, 8 alopecia areata, 4 tinea capitis, 2 discoid lupus erythematosus, 1 psoriasis vulgaris, 1 seborheic dermatitis, and 1 trichotilomania. Conclusion: Most of all dermoscope features accordance with the description in the literature, the most diagnosis is androgenetic alopecia.Key words: alopecia, dermoscope, zig-zag hair, black dots.